THU0649 PHENOTYPIC CLUSTERS OF RHEUMATIC/SYSTEMIC IMMUNE-RELATED ADVERSE EVENTS INDUCED BY CANCER IMMUNOTHERAPIES (IMMUNOCANCER INTERNATIONAL REGISTRY). (June 2019) - Ramos-Casals, Manuel; Lambotte, Oliver; Kostine, Marie; Calabrese, Leonard; Suarez-Almazor, Maria; Bingham, Clifton; Radstake, Timothy R.; Baldini, Chiara; Schaeverbeke, Thierry; Gottenberg, Jacques-Eric; Schulze-Koops, Hendrik; Leipe, Jan; et al.
Abstract : Background: The ImmunoCancer International Registry is a Big Data-Sharing multidisciplinary network focused on the research of the immune-related adverse events (irAEs) related to cancer immunotherapies (CIs). Objectives: To analyse the worldwide scenario of rheumatic/systemic autoimmune diseases (RSirAEs) associated with the use of CIs during the last 20 years. Methods: The first objective was to develop a systematic literature review crossing the CIs terms with rheumatic and systemic autoimmune diseases using MedDRAVR 15.0 terms. Results: RSirAEs were identified in 11% of 12648 patients with irAEs, including 1435 cases (30% fulfilled criteria for a systemic disease) that were classified in 5 phenotypic clusters: Non-characterized cases included myositis (25%), arthritis (12%), arthralgias (8%), sicca syndrome (7%) and vasculitis (6%); sarcoidosis (6%), myasthenia gravis (5%), polymyalgia rheumatica (4%), leukocytoclastic vasculitis (3%) and giant cell arteritis (2%) were the most frequent systemic diseases identified: In comparison with patients with organ-specific irAEs, RSirAEs were more frequently associated with combined therapies (OR 2.46, CI 2.16-2.81), checkpoint inhibitors -ICis- (OR 4.01 vs TKis, CI 3.26-4.92), and PD-1is (OR 2.46 vs CTLA4is, CI95% 2.16-2.81) Conclusion: Rheumatic/systemic irAEs can be divided into 5 phenotypic clusters: articular, muscular, granulomatous, vasculitic and systemic. These findings must be confirmed in real-life patients, and an international data-sharing ICIR registry is planned to be launched. References: : Disclosure of Interests: : Manuel Ramos-Casals: None declared, Oliver Lambotte: None declared, Marie Kostine: None declared, Leonard Calabrese Consultant for: Bristol-Myers-Squibb, Genentech and Astra-Zeneca., Maria Suarez-Almazor : None declared, Clifton Bingham Grant/research support from: BMS, Consultant for: AbbVie, BMS, Eli Lilly, Genentech/Roche, Janssen, Pfizer, Sanofi/Regeneron, Timothy R. Radstake: None declared, Chiara Baldini: None declared, Thierry Schaeverbeke: None declared, Jacques-Eric Gottenberg Grant/research support from: Bristol-Myers Squibb, Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Lilly, Pfizer, Sanofi-Genzyme, UCB Pharma, Consultant for: Bristol-Myers Squibb, Eli Lilly, UCB, Sanofi-Genzyme, Pfizer, Hendrik Schulze-Koops Grant/research support from: Novartis, Pfizer, Roche, Consultant for: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Paid instructor for: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Speakers bureau: Abbvie, Actelion, Amgen, AstraZeneca, Biogen International, BMS, Celgene, Chugai, GSK, Hospira, Janssen-Cilag, Leo Pharmaceuticals, Lilly, MSD, Medac, Merck, Novartis, Pfizer, Hexal Sandoz, Sanofi, Roche, UCB, Jan Leipe Grant/research support from: Novartis, Pfizer; Scientific Support: Novartis, Pfizer, Consultant for: AbbVie, AstraZeneca, Bristol-Myers Squibb, Celgene, Hospira, Janssen-Cilag, LEO Pharma, Lilly, Novartis, Roche, Sanofi, Speakers bureau: AbbVie, Bristol-Myers Squibb, Celgene, Janssen-Cilag, Lilly, Novartis, MSD, Pfizer, Roche, Sanofi, UCB, cassandra calabrese Speakers bureau: Regeneron/Sanofi, Pilar Brito-Zerón: None declared, Alejandra Flores-Chávez: None declared, Belchin Kostov: None declared, Soledad Retamozo: None declared, Gustavo Citera: None declared, Eva Aguilar: None declared, Michael Richter: None declared, Merav Lidar: None declared, Benjamin Fisher Consultant for: Novartis, Roche, MedImmune, Bristol-Myers Squibb, Jean-Marie Michot: None declared, David Liew: None declared, Russell Buchanan: None declared, Marte Schrumpf-Heiberg: None declared, Philippe Guilpain: None declared, Debashish Danda: None declared, Peter Olsson: None declared, Yasunori Suzuki: None declared, Saadettin Kılıçkap: None declared, Gabriela Hernandez-Molina: None declared, Virginia Fernandes Moça Trevisani: None declared, Sonja Praprotnik: None declared, Ildiko Fanny Horváth: None declared, Naoto Azuma: None declared, Berkan Armagan: None declared, Munther Khamashta: None declared, Xavier Mariette Grant/research support from: Servier, Consultant for: AstraZeneca, Bristol-Myers Squibb, GlaxoSmithKline, Janssen, Pfizer, UCB Pharma